Significant Prostate Cancer in Patients with PI-RADS Category 3 Lesions: A Single-Center, Retrospective Cohort Study - Tunç, Burçin; Gencturk, Mert; Aktürk, Adem; Kantarcı, Fatih (Urology Journal, 2023)
Purpose: The Prostate Imaging-Reporting and Data System (PI-RADS) category 3 is the most ambiguous lesion with a variable clinically significant prostate cancer (CsPCa) detection rate. Prostate-specific antigen density (PSAD) has been investigated as an adjunctive factor to improve the diagnostic efficiency of PI-RADS categories. This study aimed to investigate the utility of PSAD as an adjunctive factor in predicting CsPCA risk in patients with PI-RADS 3 lesions. Materials and Methods: The patients with an initial PI-RADS 3 category lesion (n=142) scheduled for systematic and magnetic resonance imaging-guided prostate biopsy between 2018 and 2022 were retrospectively evaluated. Demographic and clinical variables, including PSAD, were collected. The rate of CsPCa was the primary outcome. The impact of PSAD on the CsPCa detection rate was the secondary outcome. Results: The median age was 62 years. The rate of CsPCa was 8.5% (n=12). The patients with CsPCa have significantly lower prostate volüme and higher PSAD levels than those without CsPCa (p=0.016 and p=0.012). The cut-off values of PSAD in predicting CsPCa in all PI-RADS 3 patients and patients with CsPCa and clinically insignificant prostate cancer (n=26) were ≥0.181 ng/ml2. The sensitivity and specificity values for PSAD ≥0.181 ng/ml2 were of 75% (95% CI: 42.8%-94.5%) and 81.5% (95% CI: 73.4%-88.0%) in predicting CsPCa among PI-RADS 3 category. Conclusion: PSAD values higher than 0.181 ng/ml2 can be used as an adjunctive clinical parameter in predicting CsPCa in patients with PI-RADS 3 lesions and differentiating CsPCa from clinically insignificant prostate cancer cases.